Global Asymptotic Stability of Nonlinear Strict Feedback System via Backstepping Control Approach - Suka Garagara Kinwi; Stephen Ekwueme Aniaku; Christopher Chukwuma Asogwa; Emmanuel Chukwudi Mbah (International Journal of Mathematics and Mathematical Sciences)
The design of controller for nonlinear system in strict feedback form in which the equilibrium point is the origin is the focus of the study. Backstepping is the technique applied. Recursive design is used in the backstepping control technique. Using the backstepping approach, we are given a reasonably simple method to design the control law for a system with these properties. The closed-loop system’s global asymptotic stability is attained by incorporating a Lyapunov function; in this case, a quadratic one was selected for the study. To demonstrate the viability of the technique, we also performed simulations of the system and the designed control with some initial values, and positive results were reported.